Um modelo de espada criado pelos portugueses na primeira metade do século XV? - Seruca, Henrique; Barroca, Mário Jorge (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2019)
Up until now, all international arms and armour specialists have considered that swords with double guard were created in Iberia in the end of 15th century and used till the middle of 16th century. Five Portuguese iconographic documents, three religious sculptures and two sculptured tombs with dated epigraphic friezes, show that this sword model already existed in Portugal before 1440. These examples suggest that this sword model can possibly have been created in Portugal in the first half of the 15th century.